Closed cervix is associated with more severe illness in dogs with pyometra. Issue 1 (December 2016) - Jitpean, Supranee; Ambrosen, Aime; Emanuelson, Ulf; Hagman, Ragnvi
Abstract Background Pyometra, a life-threatening bacterial infection of the uterus, is classified as open or closed depending on the functional patency of the cervix i.e. presence or absence of vaginal discharge. In closed cervix pyometra, pus and bacterial products accumulate in the uterus, which is thought to induce a more severe illness. The aim of this study was to investigate whether disease severity or outcome differed in dogs with open or closed cervix pyometra. Results Prospectively collected data from 111 female dogs diagnosed with pyometra at the University Animal Hospital, Swedish University of Agricultural Sciences, Uppsala, intermittently during 2005–2012 was analyzed. Seventy-two dogs (65%) had open cervix, whereas 39 dogs (35%) had closed cervix. Differences between the two groups were explored by Wilcoxon Two Sample Test for continuous variables and Chi-square or Fisher's exact test for categorical variables.P < 0.05 was considered significant. In dogs with open cervix the median age was 9.0 years and the median weight 26.0 kg. In dogs with closed cervix the median age was 9.6 years and the median weight 25.0 kg, with no significant differences between the groups (p = 0.69 and 0.24, respectively). Five dogs (4.5%) died, all with open cervix, and 16 dogs (14%) had complications. The general physical condition was moderately or severely depressed in 30% (21/71) of dogs with open cervix (severely depressed in 4 dogs, moderately depressed in 17 dogs) and in 56% (22/39) of dogs with closed cervix (severely depressed in 3 dogs, moderately depressed in 19 dogs). The general physical condition was mildly depressed in 41 dogs with open cervix and 16 dogs with closed cervix, whereas it was normal in nine dogs with open cervix and one dog with closed cervix. None of the included dogs had very severely depressed general physical condition or were non-responsive. Leukocytosis, neutrophilia, monocytosis and moderately to severely depressed general condition was more commonly found in dogs with closed cervix (p = 0.003, p = 0.008, p = 0.003 andp = 0.006, respectively). Sepsis was more commonly present in closed cervix pyometra (77%, 30/39 dogs) compared to open cervix pyometra (51%, 36/71 dogs) (p = 0.007). Presence of prolonged postoperative hospitalization did not differ significantly between the two groups. Conclusions In dogs with closed cervix, sepsis was more common, the general physical condition more often moderately to severely depressed and leukocytosis, neutrophilia and monocytosis more frequently found. The results showed that closed cervix was associated with a more severe illness than open cervix at admission but not with poorer outcome as measured by postoperative hospitalization. These findings may be clinically valuable for optimizing monitoring and treatments in dogs with the disease.